Maqasid based approach on the role of Muslim public funds in sustaining Islamic microfinance: A case study of Tabung Masjid in Selangor, Malaysia - Zakariyah, Luqman; Ibrahim, Ahmad Basri; Md Nor, Nurhidayat; Mhd. Sarif, Suhaimi; Mohd Noor, Azman (2016)
Mosque fund, known as Tabung Masjid in Malaysia, is one of the revenues in Islam yet to be developed. The proper management of this revenue in all Muslim countries where Tabarru‘āt (voluntary donations) are collected ought to have sustainability capacity on Islamic microfinance. However, managing these funds to bring about the foreseeability remains untapped. In Selangor State of Malaysia as a case study, Tabung Masjid (TM) has not been effectively managed to serve the purpose of Islam. This is either partly due to unawareness of the Islamic jurisprudential perspectives on its potentiality or partly due to the uninformed ways of its management. This paper aims to assess ways of which Tabung Masjid in Selangor State, Malaysia is managed. The paper evaluates the management of TM in Selangor using both questionnaires and semi-structured interview to unveil the current situation of these funds. The role of these funds in strengthening Islamic microfinance is argued based on Maqasid Shariah of protection of wealth. The paper suggests a Tabung Hajj prototype of Tabung Masjid as sustainable drive of Islamic microfinance for empowering Muslim and alleviating poverty.